A Feasibility study on Biolyzer small scale biomass pyrolyzer for farm irrigation - Castro, Jessamine V.; Ngo, John William K.; Ordaniel, Rona Marie J.; Santiago, Christine Rose L. (College of Engineering, 2013)
In order to address the issue of the country's dependency on oil imports, the use of indigenous materials such as biomass is currently being developed. Biomass is any biological material derived from living organisms; which when properly utilized, can be used as renewable fuel that can significantly reduce carbon emissions. The goal of this study is to assess the market, technical and financial feasibility of the biomass pyrolyzer for farm irrigations developed by the Department of Science and Technology (DOST) under the Forest Product Research and Development Institute (FPRDI). This equipment covers biomass wastes into biomass fuel that can be used to power farm irrigations. Primary and secondary data were gathered through statistical data from the Bureau of Agricultural Statistics (BAS) and the National Irrigation Administration (NIA) and through direct surveys from farming cooperatives and individual farmers. The market was specified to be the farming cooperatives from Regions I and II. Certain marketing strategies were developed in order to penetrate the market by creating a marketing mix of product positioning, placement and promotion. Sales forecast for the next five years is projected, together with the sales and marketing costs. Analysis on the technical feasibility is done by identifying the material requirements as well the equipment and processes to be used in the production of the product Production and capacity planning were performed to determine the labor requirements for the volume of products to be produced to meet the forecasted sales. Cost analysis was made to determine the financial feasibility of the study. Costs for starting-up the company, investment investitures, and operating expenditures were determined and projected over a five-year period. After analysis, it was found out that there is an existing market for the product, hence it is market feasible. It is also technically feasible because there are suppliers available to provide the raw materials needed for the product and there is a production and office site available at a reasonable price. Aside from this, it is a viable business because the net present value computed in the study is positive, as well as the internal rate of return.